MORPHOMETRIC AND SOIL INDICATORS OF POPULATIONS ALLOCHRUSA GYPSOPHILOIDES (CARYOPHYLLACEAE) FOUND IN SYRDARYA KARATAU (Experimental biology, 2023)
As a result of field studies of Allochrusa gypsophiloides populations on the territory of Kazakhstan revealed significant reductions in the natural range of the species as a result of anthropogenic activities. Information on the current state of the species is important for clarifying the prospects of their existence. The article describes morphometric and soil indicators of populations of rare,endemic plants Allochrusa gypsophiloides.3 populations (4cenopopulations) of the species were studied.1-population-Syrdarya Karatau-Sayasu Gorge;2-population-Syrdarya Karatau-Kujik Pass;3-population-Karatau foothill plain, near the village of Birlik. Field and route-reconnaissance research methods were used to conduct the research. For correlation analysis, the height of generative individuals during flowering, the number of individuals,the number of shoots and flowers were selected to check the importance of differences between cenopopulations. The Pearson correlation assessment showed that the average height of individuals during flowering directly correlated with the number of shoots and the number of flowers of CP2, CP3 and CP4.
Keywords: Allochrusa gypsophiloides; endemic; population; cenopopulation; correlation; soil